Redescription of Phonotimpus separatus Gertsch & Davis, 1940 (Araneae: Phrurolithidae) and description of two new species of Phonotimpus from Mexico - Chamé-Vázquez, David; Ibarra-Núñez, Guillermo; Jiménez, Maria Luisa (Zootaxa, 2018)
The female of Phonotimpus separatus Gertsch & Davis (the type species of the genus) is redescribed from a specimen collected at the type locality, and two new species of Phonotimpus from Mexico are described: P. pennimani sp. nov. and P. talquian sp. nov. A more detailed description of P. separatus is provided to better distinguish them from related taxa. The two new species are closely related; males and females of both species share several somatic and genitalic characters not found in P. separatus. The resemblance of both new species to P. separatus is discussed.